High efficient upconversion luminescence of NaGdF4: Yb3+/Er3+ nanoparticle: first-principles calculation, dual-wavelength stimuli and logic gate application. (15th October 2022) - Fan, Xuemei; Huang, Wei; Ying, Weitao; Xu, Shiqing; Liu, Shimin
ABSTRACT: First-principle theory was used to design NaGdF4 :Yb 3+ /Er 3+ crystal, where the density of state, X-ray diffraction and optical coefficient had been studied through a generalised gradient approximation within density functional theory to predicate the effect of rare earth ion doping on the electronic and optical performance. Besides, NaGdF4 :Yb 3+ /Er 3+ nanoparticles were also obtained by liquid–solid–solution method and realized the enhancement of upconversion emission and the regulation of spectrum under co-excitation of the 980 nm and 1550 nm lasers. The results inspired us to establish upconversion logic gate system, where 'INHIBIT, OR, XOR, YES, AND' logic gate operations had been successfully developed by introducing external two excitation sources as input signals and monitoring the relative intensity signals of green and red emission bands and G/R ratio signal.